The nature of child labour in Zimbabwe and its effects to development: a case of Mutasa district farms in Manicaland province. - Machimbidzofa, Vesta (Midlands State University, 2017)
Child labour has become a societal problem globally which calls for attention from different institutions. International as well as national instruments have been put in place trying to address the phenomenon however, it still remains on the increase. As a result of the research the root causes of the problem was discovered to be poverty as well as orphans and vulnerable children who are now child headed because of HIV and AIDS. The major reasons of the study was to determine type of work of children in farms will be doing and the effects to development in Mutasa District farms. Qualitative design was used and purposive sampling and in Mutasa there is high incidents of child labour. Interviews and questionnaires were used to collect data. Interviews were also conducted with Simukai Child Programme an organisation that advocates for child rights in Manicaland. Education costs are not met by the rural people in Mutasa therefore increasing child labour cases. Government policies concerning child labour are having loopholes and the researcher recommend on how to curb child labour and upholds protection of child rights.